2011
DOI: 10.1111/j.1467-9922.2010.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Negative and Positive Evidence on Adult Word Learning

Abstract: This study compared negative and positive evidence in adult word learning, predicting that adults would learn more forms following negative evidence. Ninety-two native English speakers (32 men and 60 women [M age = 20.38 years, SD = 2.80]), learned nonsense nouns and verbs provided within English frames. Later, participants produced plural and past tense forms for the irregular nouns and verbs following negative or positive evidence. As anticipated, correct production followed negative evidence, and errors fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
(214 reference statements)
0
2
0
Order By: Relevance
“…This may be because the JRs indicated that they had had more exposure to English outside of class time and thus are likely to have had greater exposure to grammatically correct usage as well as explicit feedback from native speakers on their accurate use of the present perfect in real-life contexts. This may have led to better overall performance (see Iwashita, 2003;Strapp, Helmick, Tonkovich, & Bleakney, 2011). The JRs may have also been able to draw on a broader tacit understanding of grammar in the gap-fill test.…”
Section: Watanabe: Present Perfect: Effects Of Learning Environmentmentioning
confidence: 99%
“…This may be because the JRs indicated that they had had more exposure to English outside of class time and thus are likely to have had greater exposure to grammatically correct usage as well as explicit feedback from native speakers on their accurate use of the present perfect in real-life contexts. This may have led to better overall performance (see Iwashita, 2003;Strapp, Helmick, Tonkovich, & Bleakney, 2011). The JRs may have also been able to draw on a broader tacit understanding of grammar in the gap-fill test.…”
Section: Watanabe: Present Perfect: Effects Of Learning Environmentmentioning
confidence: 99%
“…14 specific manner-of-motion verbs were selected and taught in this session so that students would have resources beyond the basic swim, jump, and run which dominated preintervention writing samples (please see Appendix A for a list of manner-of-motion verbs taught in this lesson). Once the manner-of-motion verbs had been taught, the participants were provided with negative evidence (Larrañaga, Treffers-Daller, Tidball, & Gil Ortega, 2012;Strapp, Helmick, Tonkovich, & Bleakney, 2011) for the first time. Examples of negative evidence included the children crossed the lake swimming and the boy passes over the cat jumping.…”
Section: Methodsmentioning
confidence: 99%